Global birth prevalence of major congenital anomalies: a systematic review and meta-analysis - Xiaolong Xie; Jiao Pei; Li Zhang; Yang Wu (BMC Public Health)
Abstract Background There is a lack of systematic review on the global prevalence of major congenital anomalies. We performed a systematic review and meta-analysis of population-based studies on global birth prevalence of eight major congenital anomalies (esophageal atresia, congenital diaphragmatic hernia, duodenal atresia, intestinal atresia, gastroschisis, omphalocele, Hirschsprung’s disease and anorectal malformation). Methods Population-based studies reporting the birth prevalence of these anomalies were included from 1969 to 2024. Data from eligible studies were pooled in meta-analysis to get global estimates of birth prevalence and prevalence in subgroups of geographic regions, countries with varying income levels and time periods. Results One hundred and twenty-three studies including a total of 256,507 cases of congenital anomalies and 769,455,220 births were included in this study. Overall birth prevalence of theses eight anomalies ranged from 0.86 to 3.11 cases per 10,000 births. Anorectal malformation had the highest birth prevalence among these anomalies with 3.11 cases (95% confidence intervals (CI): 2.77–3.50) per 10,000 births. Birth prevalence of congenital diaphragmatic hernia had a great decrease from 4.19 per 10,000 births in the 1960s to 1.30 per 10,000 births in the 2020s. Omphalocele had high prevalence in Africa and low-income countries. Conclusion This systematic review summarizes birth prevalence of eight major congenital anomalies. The burdens of these anomalies had variations in the world. Information of this study could help with better understanding of epidemiology and etiology of these anomalies.